CONFLICT MANAGEMENT BY USING THE POSSIBILITIES OF COORDINATED OPTIMIZATION TO ACHIEVE SUSTAINABLE DEVELOPMENT OF ORGANIZATIONAL SYSTEMS: CONFLICT MANAGEMENT BY USING THE POSSIBILITIES OF COORDINATED OPTIMIZATION TO ACHIEVE SUSTAINABLE DEVELOPMENT OF ORGANIZATIONAL SYSTEMS - Кrachunov Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
An analysis of the interests of the subjects in carrying out appropriate activities in which there is an exchange of goods and benefits is made in this research. The most common types of subjects and their target functions are identified in terms of opportunities for coherent optimization of their interests. Some opportunities for application of the principle of the agreed optimum for conflict management and sustainable development of the organizational and production systems are considered. Opportunities for building coalitions of entities working on the principle of the agreed optimum are also presented, which can be applied in modeling, measuring and managing business processes in the organizations and in building a strategic vision for the development of flexible manufacturing enterprises. Findings and conclusions are made about the applicability of the research.